METHODOLOGY FOR SELECTING PRIORITY REGIONAL CLUSTER DEVELOPMENT (the Volgograd region as the example) - L. V. Dmitrieva (Модернизация, инновация, развитие)
Selecting priority of the creation of clusters is a highly relevant task at the present time, in the context of limited resources for regional development. This article discusses the complex methodology takes into account the macroand microeconomic approach, the specific structure of regional economy, the competitiveness of enterprises and products, and the potential of the investments projects, taking into account both the progress of the regional economic system and its potential for development through existing investment projects.